Evaluation of physiological traits and flowering in Cucumis sativus L. by foliar application of chitosan at three sowing dates grown under hot environment - Ali, Mujahid; Ayyub, Chaudhary Muhammad; Silverman, Emily; Rehman, Malik Abdul; Iqbal, Shahid; Hussain, Zahoor; Nawaz, Muhammad Azher; Bazmi, Muhammad Sultan Ali (Journal of Pure and Applied Agriculture, 2023)
Heat stress is a major issue in tropical and subtropical regions of the world where vegetable crops are grown. Utilizing genetic diversity, two tolerant (L3466 and Desi-cucumber) and two susceptible (Suyo Long and Poinsett) genotypes were grown under field conditions in three sowing times (15th March, 1st April, and 15th April). Chitosan (CHT) (200 ppm) was exogenously applied on foliage at 30 days’ post sow (DPS) and then twice more in one-week intervals. The peak temperature recorded in May was 47.8°C, 48.0°C in June, and 46.1°C in July, respectively. There was a significant difference in means of sowing dates, the first sowing date had the highest leaf turgor potential. Both Suyo Long (0.106 MPa) and Poinsett (0.126 MPa) responded more efficiently to CHT application in the first sowing date compared with non-treated CHT plants. In the first sowing date, the heat-tolerant genotypes treated with CHT had lower leaf water loss; Desi-cucumber had the lowest water loss with a transpiration rate of 2.97 mmol m-2 s -1 followed by L3466, 3.07 mmol m-2 s -1 , respectively. During the third sowing date, non-treated Poinsett had the highest transpiration rate of 4.38 mmol m-2 s -1 followed by Suyo Long with 4.18 mmol m-2 s -1 . Heat-sensitive genotypes had higher transpiration rates, lost more water at high temperatures which led to wilting of plants in the 3rd sowing date. Similarly, Desi-cucumber (10.54) had the most female flowers, at par with L3466 (10.19) with CHT application during the first sowing date. So, Desi-cucumber (6.63) exhibited the highest number of fruits by L3466 (6.40) with CHT treated plants, while Suyo Long (5.78) and Poinsett (5.53) showed significantly low in the number regarding CHT treated plants. For cucumber production, CHT treatment proved helpful to increase the yield potential grown under hot environments. © 2021 Department of Agricultural Sciences, AIOU